Environmental Disinfection Strategies to Prevent Indirect Transmission of SARS-CoV2 in Healthcare Settings - Dorina Lauritano; Giulia Moreo; Luisa Limongelli; Michele Nardone; Francesco Carinci (Applied Sciences, 2020)
(1) Introduction: The novel respiratory syndrome coronavirus 2 (SARS-CoV-2), also called coronavirus disease 2019 (COVID-19), is rapidly spreading in many countries and represents a public health emergency of international concern. The SARS-CoV-2 transmission mainly occurs from person-to-person via respiratory droplets (direct transmission route), leading to the onset of mild or severe symptoms or even causing death. Since COVID-19 is able to survive also on inanimate surfaces for extended periods, constituting an indirect transmission route, healthcare settings contaminated surfaces should be submitted to specific disinfection protocols. Our review aimed to investigate the existing disinfection measures of healthcare settings surfaces, preventing the nosocomial transmission of SARS-CoV-2. (2) Materials and Methods: We conducted electronic research on PubMed, Scopus, Science Direct, and Cochrane Library, and 120 items were screened for eligibility. Only 11 articles were included in the review and selected for data extraction. (3) Results: All the included studies proposed the use of ethanol at different concentrations (70% or 75%) as a biocidal agent against SARS-CoV-2, which has the capacity to reduce the viral activity by 3 log10 or more after 1 min of exposure. Other disinfection protocols involved the use of chlorine-containing disinfectant, 0.1% and 0.5% sodium hypochlorite, quaternary ammonium in combination with 75% ethanol, isopropyl alcohol 70%, glutardialdehyde 2%, ultraviolet light (UV-C) technology, and many others. Two studies suggested to use the Environmental Protection Agency (EPA)-registered disinfectants, while one article chooses to follow the WST-512-2016 Guidance of Environmental and Surfaces Cleaning, Disinfection and Infection Control in Hospitals. (4) Conclusion: Different surface disinfection methods proved to reduce the viral activity of SARS-CoV-2, preventing its indirect nosocomial transmission. However, more specific cleaning measures, ad hoc for the different settings of the healthcare sector, need to be formulated.